Effects of glatiramer acetate on chemokine expression in EAE models immunized with different myelin antigens - Bulut, S.; Akbulut, H. H.; Kilic, H.; Ozden, M.; Berilgen, M. S. (Wiley-Blackwell, 2008)
[Abstract Not Available]
12th Congress of the European-Federation-of-Neurological-Societies -- AUG 23-26, 2008 -- Madrid, SPAIN